Pollyanna - Porter, Eleanor H. (Eleanor Hodgman) 1868-1920.; Leighton, Marion (New York Baronet Books., 1995)
When orphaned, eleven-year-old Pollyanna comes to live with austere and wealthy Aunt Polly, her philosophy of gladness brings happiness to her aunt and other unhappy members of the community.
Keywords: Orphans -- Fiction; Aunts -- Fiction; Conduct of life -- Fiction; Cheerfulness -- Fiction; Interpersonal relations -- Fiction; Vermont -- History -- 20th century -- Fiction